(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
Ensuring the economic security of the banking sector is paramount for the sustainable development of the country’s economy. It involves regulating financial activities, managing the money supply, and enhancing the stability of banks’ operations. While there are various methods for assessing the financial security of banks, adherence to regulations set by the Central Bank of the Republic of Uzbekistan is essential. Meeting these requirements helps banks control potential risks associated with their operations. To enhance the economic security of modern banks, the paper proposes evaluating changes in their financial stability based on indicators such as capital adequacy, liquidity, asset volume, and profitability.